The analysis of latent fingermark chemistry using fourier=transform infrared spectroscopy - Johnston, Andrew (Cranfield University, 2018)
Latent fingerprints are comprised of a complex mixture of orfanic and inorganic components that exhibit broad chemical variability. Fingermarks are dynamic compositions prone to degradation over time and in varying environmental conditions. The complexity of latent fingermark chemistry has led to an abundance of literature over a number of years utilizing various analytical techniques, which have endeavoured to provide a greater understanding of these complex chemical systems. In particular, a key focus has been on fingermark decomposition and with recent advances in analytical instrumentation a more in-depth understanding of the dynamics of fingermark chemistry has been achieved despite this, there remain significant gaps in the literature. The work presented within this thesis looks at various aspectsof latent fingermark chemistry that aim to address these gaps. During this research the capabilities and limitations of Fourier-Transform Infrared (FTIR) spectromicroscopy were compared to the more established analytical technique of gas chromatography-mass spectrometry for the analysis of latent fingermarks. A novel approach to analysing the change in latent fingermark chemistry over time at various moderate temperatures was demonstrated. An investigation into the intermolecular interactions of lipid components within simplified analogue “fingermark” solutions was conducted, and the implications of these interactions for natural fingermark chemistry considered. Finally the temporal degradation of illicit substances in latent fingermarks using Spectroscopic imaging was investigated. The results of this study, structured in the form of four research papers, demonstrate the complexity of latent fingermark composition, variability, and analysis. The issue FTIR spectromicroscopy to study in-situ, real-time changes in fingermark chemistry subjected to varying temperatures showed that total composition is affected by temperatures above 50oC, and oxidation mechanisms take place almost immediately after deposition, even ar room temperature. The use of simplified analogue fingermark solutions to study intermolecular interactions within natural fingermarks identified two key components, squalene and cholesterol, that potentially affect downstream organic interactions post-deposition. Finally spectroscopic imaging successfully identified and spatially mapped aged illicit substances present within latent fingermarks up to thirty days post- deposision. It was also possible to quantify degradation of those illicit compounds over time. Due to the different facets of this research, the results of this thesis are expected to have an impact on a broad range of disciplines both qithin academia and fo more piratical forensic applications.